Geschiedenis voor en tijdens IIe wereldoorlog - het verzet - Corijn, Herman; Puttemans, Jul; Van Calsteren, Jan; Gijsels, Hugo
"Herman, Corijn , Jul Puttemans, Jan Van Calsteren, Hugo Gijsels Losbladig werk"